Clinical evaluative value of cervical magnetic resonance T2 axial image in the severity of cervical canal stenosis - FEI Changjun*，CHEN Bing，XIA Shiyong，ZHANG Xiaoyong，XIA Yiqiu，LI Hongxia (Zhongguo linchuang yanjiu)
Objective To explore the clinical value of cervical magnetic resonance T2 axial image in evaluating thedegree of cervical canal stenosis，in order to guide precise clinical diagnosis and treatment. Methods The clinical data of 80 patients with cervical spondylosis admitted to the Third Affiliated Hospital of Anhui Medical University from June 2021 to June 2024 were selected. All patients underwent magnetic resonance imaging（MRI）to detect the cervical spinal canal，and image analysis was performed. The effective sagittal spinal canal（ESSC）of the spinal canal was measured by identifying the most severely compressed planes in the C3⁃C7 segments on the T2 axial MRI of the cervical spine. The ESSC of patients with varying degrees of cervical spinal stenosis in each segment of C3⁃C7 was analyzed，and Spearman correlation analysis was performed to examine the correlation between the grading of each segment of C3⁃C7 and the degree of cervical spinal stenosis. Results Imaging examination of 80 patients with spinal canal stenosis showed that 34 cases（42.50%）were grade 0，26 cases（32.50%）were grade 1，and 20 cases（25.00%）were grade 2⁃3. The average ESSC value of patients with grade 0 cervical spinal stenosis was（10.62±1.12）mm，grade 1 patients was（9.41±0.97）mm，and grade 2⁃3 patients was（8.59±0.93）mm. As the degree of cervical spinal stenosis increased，the ESSC value gradually decreased（F=26.302，P<0.01）. In the C3 to C7 segments，the ESSC values were positively correlated with the degree of cervical spinal stenosis（P<0.05）. Conclusion The ESSC values in the T2 axial image of cervical magnetic resonance gradually decrease with the degree of cervical spinal canal stenosis，which have certain practical value.